Sugar Composition of Apricot Fruit Oligosaccharides - Muhidinov, Zayniddin (Central Asian Journal of Medical and Natural Science, 2025)
Apricot pomace, a byproduct of fruit processing, is a rich source of pectin-derived oligosaccharides (POS) with potential applications in functional foods and nutraceuticals. This study aimed to characterize the sugar composition of POS fractions from apricot pomace using hydrolysis-extraction by high-performance liquid chromatography with refractive index detection (HPLC-RI). The analysis revealed that glucose (31–39%) and arabinose (24–37%) were the dominant sugars in all fractions, followed by maltose (16–20%) and sucrose (6–15%), with trace amounts of galactose and rhamnose detected in specific fractions. The highest yield of POS (12.7%) was obtained in the fraction isolated through membrane filtration. Compared to other fruit-derived POS, apricot POS exhibited a unique sugar profile dominated by arabinose, suggesting significant prebiotic potential. These findings highlight the value of apricot pomace as a sustainable source of bioactive compounds and provide a basis for further research into its structural and functional properties.